2001
DOI: 10.1023/a:1006478317173
|View full text |Cite
|
Sign up to set email alerts
|

Continued Breast Cancer Risk Reduction in Postmenopausal Women Treated with Raloxifene: 4-Year Results from the MORE Trial

Abstract: Raloxifene, a selective estrogen receptor modulator approved for the prevention and treatment of postmenopausal osteoporosis, has shown a significant reduction in breast cancer incidence after 3 years in this placebo-controlled, randomized clinical trial in postmenopausal women with osteoporosis. This article includes results from an additional annual mammogram at 4 years and represents 3,004 additional patient-years of follow-up in this trial. Breast cancers were ascertained through annual screening mammogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
302
0
24

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 607 publications
(343 citation statements)
references
References 22 publications
15
302
0
24
Order By: Relevance
“…Raloxifene was shown to reduce breast cancer risk regardless of lifetime estrogen exposure, but the reduction was greater in those with higher lifetime exposure to estrogens [117]. Whether this benefit is due to a decrease in carcinogenesis or to lower tumor growth will be specified in the next few years.…”
Section: Raloxifene and Tamoxifen Comparisonmentioning
confidence: 99%
“…Raloxifene was shown to reduce breast cancer risk regardless of lifetime estrogen exposure, but the reduction was greater in those with higher lifetime exposure to estrogens [117]. Whether this benefit is due to a decrease in carcinogenesis or to lower tumor growth will be specified in the next few years.…”
Section: Raloxifene and Tamoxifen Comparisonmentioning
confidence: 99%
“…[31] Raloxifene was not shown to significantly reduce the risk of non-vertebral fractures. However, raloxifene reduced the risk of invasive breast cancer by 72% (CI 54%-83%) [119]. In a patient subgroup (13.4% of the patients in the study) at high risk of cardiovascular events, the MORE study reported a 40% reduction in the risk of cardiovascular events (CI 5%-62%) [120].…”
Section: Clinical Datamentioning
confidence: 89%
“…The mean femoral neck T-score for bone mineral density (BMD) was -2.33 SD and for the lumbar spine the BMD was T-score of -2.58 SD. [31,39,119,120]. Patients were randomly assigned to receive 60 mg/d or 120 mg/d of raloxifene or matching placebo.…”
Section: Clinical Datamentioning
confidence: 99%
“…[131,132]. The anticipated result in reducing the risk of breast cancer as a beneficial side effect of treating osteoporosis propelled raloxifene into clinical trial vs. tamoxifen for the prevention of breast cancer as the primary endpoint.…”
Section: Selective Estrogen Receptor Modulation and Chemopreventionmentioning
confidence: 99%
“…A use patent for the treatment and prevention of osteoporosis was filed by Eli Lilly in 1992. Raloxifene has now been available for the treatment and prevention of osteoporosis in postmenopausal women since 1999 based on the prospective clinical trials demonstrating an approximately 40% decrease in spinal fractures [130] with the advantage over hormone replacement therapy of causing a 70% decrease in the incidence of breast cancer [131,132]. The anticipated result in reducing the risk of breast cancer as a beneficial side effect of treating osteoporosis propelled raloxifene into clinical trial vs. tamoxifen for the prevention of breast cancer as the primary endpoint.…”
Section: Selective Estrogen Receptor Modulation and Chemopreventionmentioning
confidence: 99%